CD8+ T‐cell senescence and skewed lymphocyte subsets in young Dyskeratosis Congenita patients with PARN and DKC1 mutations. Issue 9 (25th May 2020) - Zeng, Ting; Lv, Ge; Chen, Xuemei; Yang, Lu; Zhou, Lina; Dou, Ying; Tang, Xuemei; Yang, Jun; An, Yunfei; Zhao, Xiaodong
Abstract: Background: Dyskeratosis congenita (DC) is a syndrome resulting from defective telomere maintenance. Immunodeficiency associated with DC can cause significant morbidity and lead to premature mortality, but the immunological characteristics and molecular hallmark of DC patients, especially young patients, have not been described in detail. Methods: We summarize the clinical data of two juvenile patients with DC. Gene mutations were identified by whole‐exome and direct sequencing. Swiss‐PdbViewer was used to predict the pathogenicity of identified mutations. The relative telomere length was determined by QPCR, and a comprehensive analysis of lymphocyte subsets and CD57 expression was performed by flow cytometry. Results: Both patients showed typical features of DC without severe infection. In addition, patient 1 (P1) was diagnosed with Hoyeraal‐Hreidarsson syndrome due to cerebellar hypoplasia. Gene sequencing showed P1 had a compound heterozygous mutation (c.204G > T and c.178‐245del) in PARN and P2 had a novel hemizygous mutation in DKC1 (c.1051A > G). Lymphocyte subset analysis showed B and NK cytopenia, an inverted CD4:CD8 ratio, and decreased naïve CD4 and CD8 cells. A significant increase in CD21 low B cells and skewed numbers of helper T cells (Th), regulatory T cells (Treg), follicular regulatory T cells (Tfr), and follicular helper T cells (Tfh) were also detected. Short telomere lengths, increased CD57 expression, and an expansion of CD8 effector memory T cells re‐expressing CD45RA (TEMRA) were also found in both patients. Conclusion: Unique immunologic abnormalities, CD8 T‐cell senescence, and shortened telomere together as a hallmark occur in young DC patients before progression to severe disease.